Camille Pissarro: father of Impressionism - Whiteley, L; Harrison, C (Ashmolean Museum, 2022)
Camille Pissarro (1830–1903) is one of the most celebrated artists of 19th-century France and a central figure in Impressionism. Considered a father-figure to many in the movement, his work was enormously influential for many artists, including Claude Monet and Paul Cézanne. This major exhibition, of works drawn from the Ashmolean's collections as well as international loans, will span Pissarro's entire career. Pissarro continued to explore and refine his approach and technique throughout his life. The exhibition will look at how he responded to the previous generation of artists including Corot and Daubigny, to his relationship with the Impressionists with whom he allied himself and encouraged in the face of rejection by the established art world. Never ceasing to question his method, he developed close working relationships with Gaugin, for whom he was a mentor, and Cézanne for whom he was both teacher and pupil. It also includes a section on his family life – he was a devoted husband and father and his four sons all became artists. The Ashmolean has numerous sketches and photographs of the family.